Adjuvant treatment for resected pancreatic adenocarcinoma: A systematic review and network meta-analysis. (January 2020) - Parmar, Ambica; Chaves-Porras, Jorge; Saluja, Ronak; Perry, Kaitlyn; Rahmadian, Amanda P.; Santos, Seanthel Delos; Ko, Yoo-Joung; Berry, Scott; Doherty, Mark; Chan, Kelvin K.W.
Highlights: Recurrence is common following surgical resection for pancreatic adenocarcinoma. Seven chemotherapy strategies have demonstrated improvements in survival outcomes. Through indirect comparison, mFOLFIRINOX is the most efficacious adjuvant chemotherapy. For mFOLFIRINOX ineligible, S1 should be considered in Asian populations. For non-Asian, mFOLIFIRINOX ineligible patients, gemcitabine-capecitabine is preferred. Abstract: Adjuvant chemotherapy has significantly improved outcomes following surgical resection for pancreatic adenocarcinoma; however, the optimal adjuvant strategy remains unclear. This systematic review and network meta-analysis was conducted to provide indirect comparative evidence across adjuvant chemotherapies. Electronic searches of EMBASE, MEDLINE, Cochrane and ASCO databases were conducted to identify eligible randomized controlled trials (RCT). Direct pairwise meta-analysis was conducted for disease-free survival (DFS), overall-survival (OS) and adverse events (AE). Network meta-analysis of DFS and OS was conducted to evaluate indirect comparisons. Ten publications of eleven RCT met eligibility criteria. Indirect DFS comparison demonstrated superiority of mFOLFIRINOX versus gemcitabine-capecitabine, gemcitabine-erlotinib and gemcitabine-nab-paclitaxel. S-1 demonstrated a DFS benefit versus gemcitabine-capecitabine, gemcitabine-erlotinib, gemcitabine-nab-paclitaxel. OS benefits were demonstrated for mFOLFIRINOX verus gemcitabine-erlotinib and for S-1 versus gemcitabine-based combination with erlotinib, capecitabine and nab-paclitaxel. In conclusion, mFOLFIRINOX is the preferred approach for adjuvant therapy. For mFOLFIRINOX-ineligible patients no additional benefit is seen with gemcitabine-nab-paclitaxel.